Bactericidal effects of 8,9-dihydroxy-1,5,6,10b-tetrahydropyrrolo[2,1-a]isoquinolin- 3(2H)-one (Trolline) on selected entero-pathogenic bacteria - Sadiq, Masud Eneji; S, Abdullahi Mikailu (International Journal of Pharmacological Research, 2017)
The activity of the compound 8,9-dihydroxy-1,5,6,10b-tetrahydropyrrolo[2,1-a]isoquinolin-3(2H)-one (trolline) isolated from Mirabilis jalapa against selected enteropathogenic bacteria is being investigated. Clinical isolates of Streptococcus feacalis, Shigella dysenteriae, Salmonella typhi, Bacillus cereus, Eschericia coli and Vibrio cholera were screened for susceptibility to serial dilutions of an initial stock concentration of 100g/ml (456.62M) of the compound. Zones of inhibition on well labeled sub-cultured agar plates were measured in millimeters and recorded. The minimum inhibitory concentration (MIC) was determined using broth dilution methods while the least concentration that killed the bacterial cells was recorded as the minimum bactericidal concentration (MBC). S. typhi, B. cereus, E. coli and S. dysenteriae were susceptible to the test compound, with zones of inhibition measuring 32mm for S. dysenteriae. MIC of 57M was observed for S. typhi, B. cereus and S. dysenteriae while bactericidal concentration (MBC) ranged between 114-228M for all susceptible organisms tested. In conclusion, the in-vitro assessment of trolline shows the compound possess bioactive properties against diarrhea causing enteropathogenic bacteria.